2010
DOI: 10.1259/bjr/74949757
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ADC value in the characterisation of renal carcinoma by diffusion-weighted MRI

Abstract: ABSTRACT. The purpose of this study is to evaluate the role of diffusion-weighted imaging (DWI) in combination with T 1 and T 2 weighted MRI for the characterisation of renal carcinoma. The institutional review board approved the study protocols and waived informed consent from all of the patients. 47 patients (32 male and 15 female; age range, 21-85 years; median age, 65 years) who had suspected renal lesions on abdominal CT underwent MRI for further evaluation and characterisation of the lesions from April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…ADCs of renal tumor obtained with 3T MRI tended to be lower than those obtained with 1.5T MRI. The ADC of clear cell RCC with 1.5T MRI was reported to be within the range of 1.54-1.85 © 10 -3 mm 2 /s, [15][16][17][18]20 and between 1.381-1.698 © 10 -3 mm 2 /s with 3T MRI; In our study, the ADC was 1.423 © 10 -3 mm 2 /s. The ADC of AML with 1.5T MRI was reported to be within the range of 0.74 -1.58 © 10 -3 mm 2 /s.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…ADCs of renal tumor obtained with 3T MRI tended to be lower than those obtained with 1.5T MRI. The ADC of clear cell RCC with 1.5T MRI was reported to be within the range of 1.54-1.85 © 10 -3 mm 2 /s, [15][16][17][18]20 and between 1.381-1.698 © 10 -3 mm 2 /s with 3T MRI; In our study, the ADC was 1.423 © 10 -3 mm 2 /s. The ADC of AML with 1.5T MRI was reported to be within the range of 0.74 -1.58 © 10 -3 mm 2 /s.…”
Section: Discussionsupporting
confidence: 54%
“…With regard to MRI, diffusion-weighted MRI (DWI) has recently been used to differentiate different subtypes of RCC and fat poor AML and clear cell RCC. [15][16][17][18][19][20] However, almost all these studies were performed using MRI at 1.5T. To date, only 2 studies, which examined only RCC but not benign renal tumors, have used MRI at 3T.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Use of diffusion-weighted MRI also allowed separation of clear RCC and nonclear RCC. 39 Additionally, dynamic contrast-enhanced MRI was able to detect vascular changes induced by sunitinib in xenograft renal tumors, demonstrating the potential utility of dynamic contrast-enhanced MRI in selecting the dose and schedule of angiogenic compounds. 40 Guimaraes et al 41 have shown the ability to identify metastatic lymph node in renal carcinoma using lymphotrophic nanoparticle-enhanced MRI.…”
Section: Renal Biopsy and Imagingmentioning
confidence: 97%
“…Manenti et al (77) have reported significant differences among the ADC values of renal carcinomas and normal parenchyma; however, their analysis did not reveal a significant difference in the mean ADC value of the individual histological variants of renal carcinoma. In another study, Paudyal et al (78) demonstrated that ADC values were significantly higher in renal cell carcinomas (RCC) than in transitional cell carcinomas. Further analysis of the histological subtypes of RCC demonstrated that clear-cell carcinomas had lower ADC values than non-clear-cell carcinomas, most likely because of differences in cellularity.…”
Section: Abdominal Applicationsmentioning
confidence: 99%